Analisis Implementasi Program Pelatihan dan Pengembangan Karyawan di J4 Hotels Legian - Ni Luh Putu Siki Widiasih; I Putu Yoga Laksana; I Nyoman Hendra Laksmana (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The hospitality industry requires competent human resources to deliver excellent service. However, the gap between training blueprints and empirical operational realities frequently triggers persistent guest complaints, potentially harming the hotel's reputation in Bali's hypercompetitive tourism market. This research aims to evaluate the effectiveness of employee training and development programs at J4 Hotels Legian using the CIPP (Context, Input, Process, Product) evaluation framework. This study utilizes a qualitative approach with a descriptive phenomenological design. Data sources comprise primary and secondary data. Informants were selected through purposive sampling, involving four key department managers (F&B, Housekeeping, Front Office, and HRD). Data were collected via in-depth semi-structured interviews, covert non-participatory observations, and documentation studies. Data analysis was conducted interactively and validated using method and source triangulation. The CIPP analysis reveals that the Context dimension aligns with operational problem-solving needs. However, the Input dimension exposes a lack of leadership cultivation modules. In the Process dimension, significant temporal friction occurs due to conflicting training schedules and operational surges. Consequently, for the Product dimension, while mechanical work speed improved, the program remains ineffective in resolving guest complaints regarding assertive communication and frontline staff initiative during crises. Kesimpulan/Implikasi] In conclusion, the training implementation is suboptimal due to methods clashing with daily work rhythms. These findings imply that management must promptly apply adaptive strategic interventions. This study recommends transitioning toward immersive simulation methodologies, micro-learning digitalization, and continuous leadership incubation.